2011
DOI: 10.1007/s13361-011-0165-1
|View full text |Cite
|
Sign up to set email alerts
|

Negative Ion Fragmentation of Cysteic Acid Containing Peptides: Cysteic Acid as a Fixed Negative Charge

Abstract: We present here a study of the collision induced dissociation (CID) of deprotonated cysteic acid containing peptides produced by MALDI. The effect of cysteic acid (C ox ) position is interrogated by considering the positional isomers, C ox LVINVLSQG, LVINVLSQGC ox , and LVINVC ox LSQG. Although considerable variation between the CID spectra is observed, the mechanistic picture that emerges involves charge retention at the deprotonated cysteic acid side chain. Fragmentation occurs in the proximity of the cystei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…In addition, experimental investigations on Cys oxidation also confirmed that the oxidation of Cys residues of proteins caused by ROS (such as H 2 O 2 ) mostly results in negatively charged CYOs. 39 …”
Section: Computational Detailsmentioning
confidence: 99%
“…In addition, experimental investigations on Cys oxidation also confirmed that the oxidation of Cys residues of proteins caused by ROS (such as H 2 O 2 ) mostly results in negatively charged CYOs. 39 …”
Section: Computational Detailsmentioning
confidence: 99%
“…Positive‐ and negative‐ion fragmentation pathways of peptides can be very different and they can thus provide useful complementary structural information . In addition, the negative‐ion fragmentation reactions of peptides are useful in the identification of post‐translational modifications as well as in peptide sequencing due to the more complete series of backbone product ions …”
mentioning
confidence: 99%
“…Analysis of fragment spectra of the other cross-linked NF1 peptides provided additional technical characterization of fliX-MS. Both C104 and C163 were trioxidated to cysteic acid, likely as a result of sample preparation under nonreducing conditions [34][35][36] (Fig. 4f-g).…”
Section: Resultsmentioning
confidence: 99%